2023
DOI: 10.1002/cjp2.326
|View full text |Cite
|
Sign up to set email alerts
|

Dual epigenetic changes in diabetes mellitus‐associated pancreatic ductal adenocarcinoma correlate with downregulation of E‐cadherin and worsened prognosis

Abstract: Diabetes mellitus (DM) is a risk factor for pancreatic ductal adenocarcinoma (PDAC) that promotes the promoter methylation of CDH1. It is still unclear whether DM can exert other epigenetic effects, such as altering microRNA (miR) expression, in PDAC. The expression of miR‐100‐5p is known to be changed in DM patients and can suppress the expression of E‐cadherin. In this study, the correlation between DM status and dual epigenetic changes was evaluated in PDAC specimens from patients who underwent radical surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…For miRNAs prioritized by the EPI, we observed the upregulation of hsa-miR-100–5p in PAAD [35] . Extensive research has shown that hsa-miR-133a–3p is downregulated in several cancers, including BRCA [36] , COAD and READ [37] , LIHC [38] , STAD [39] and others, aligning with our findings ( Fig.…”
Section: Discussionmentioning
confidence: 87%
“…For miRNAs prioritized by the EPI, we observed the upregulation of hsa-miR-100–5p in PAAD [35] . Extensive research has shown that hsa-miR-133a–3p is downregulated in several cancers, including BRCA [36] , COAD and READ [37] , LIHC [38] , STAD [39] and others, aligning with our findings ( Fig.…”
Section: Discussionmentioning
confidence: 87%